Epistimologi Penetapan Masa Haidh Istri melalui Pendekatan Ilmu Qiraat al-Quran dalam Perhitungan Masa Haidh Istri : (Studi Tekstualitas Hukum Islam dalam QS. al-Baqarah [2]: 222) - Raden Nurhayati; Denden S. Hadi Wijaya (Lajnah Ta'lif wan Nasyr Nahdlatul Ulama (LTN-NU) Kabupaten Probolinggo, 2021)
The birth of Islamic law schools in the study of jurisprudence such as the Shafi'iyah, Malikiyah, Hanbaliyah, Hanafiyah, Zhahiriyah, and so on is an implication of the differences in qiraat in the verses of the Quran. They interpreted the verses of the Quran with the basic raw material being instructions on the qiraat ordinances which were complemented by the rules of irab, shighat, and grammatical arrangements of arabic linguistic rules. The research uses a qualitative approach with a library research method approach. The purpose of this study is to understand the methodology of taking Islamic law carried out by mujtahid fiqh; and how the form of the legal product resulted from the difference in qiraat. The results of this study show that the legal case of differences in qiraat to the legal status of a wife who is menstruating (QS. al-Baqarah: 222) which gives birth to three different interpretations, namely: The Hanafi Imam School is of the view that a wife is considered holy from the menstrual state, if her menstrual blood has stopped. The jumhur school/majority of scholars consisting of imams Maliki, Shafi'i, and Hanbali are of the view that the sacred condition of a wife who is menstruating is that when she has done a big bath, then a husband is justified to take her captive. It is not permissible for the husband to take care of a wife, even though she has stopped her menstrual blood, but the wife has done a big bath. Mazhab al-Thawas and al-Mujahid argue that it is permissible for the husband to treat his wife who is menstruating by washing the wife's, then she is in the form and allowed to perform prayers immediately.